Building school library networks using open source technology: teacher-librarians' awareness and perception - Raja Ismail, Nik Roslina; Mansor, Yushiana (2014)

(untitled)
Collaborative bibliographic network among Malaysian school libraries is important in today's digital environment. The libraries must gain its role as primary information provider to its users given the fact that technology had grown so fast and at a cheaper price. However, teacher-librarians must first appreciate the value of resource sharing where resources are collaboratively shared between similar type of institutions. Therefore, the awareness and perception of the teacher-librarians towards the establishment of school library networks as well as the application of open source solutions in materialising the project would be useful in strategising appropriate actions.